Attitudes to illegal behaviours and conservation in western Tanzania - Wilfred, P; Milner-Gulland, E; Travers, H (Cambridge University Press, 2017)
Natural resources in and around protected areas in many countries in Africa are under intense pressure as a result of illegal behaviours, such as fishing, hunting and logging. A better understanding of local views on the nature of illegal behaviours and relevance of conservation actions would considerably inform conservation decisions. We gathered information on the attitudes and perceptions of communities residing around Ugalla Game Reserve in western Tanzania towards illegal behaviours and the effectiveness of conservation practices, using household surveys, key informants, and focus groups. We found that Ugalla reserve was an important source of local livelihoods (e.g. fishing, logging and beekeeping), and >45% of respondents were happy that it existed. Nonetheless, the reserve was illegally used by local people, especially for hunting (28%; SE 6) and logging (20%; SE 5). Other behaviours that were problematic for conservation included setting wildfires (13%), extensive tobacco farming (10%) and grazing (8%) that people perceived as causing extensive vegetation damage in the partially protected areas around Ugalla. Local communities felt isolated, harassed and intimidated by approaches used to protect Ugalla. They were angered at Ugalla being conserved as a trophy hunting site for foreigners, and excessive force and beatings used by game rangers to keep them away from it. Improving local livelihoods (17%), participatory conservation (16%), and giving some land to people for their agricultural activities (16%) were among the ways that local communities felt would reduce illegal activities. Our study suggests the need for conservation measures to benefit local communities around Ugalla transparently and equitably. Outreach programs would help to raise conservation awareness and attract positive attitudes towards conservation. To encourage local support for conservation, we also suggest conservation authorities create and maintain good relations with villagers near the reserve.